Advanced part-load control strategies for the Allam cycle. (5th March 2020) - Zaryab, Syed Ali; Scaccabarozzi, Roberto; Martelli, Emanuele
Highlights: Part load model of the Allam cycle has been developed. Four different part-load control strategies have been compared down to 15% load. Part-load efficiency can be maximized by adopting optimized minimum cycle pressure. Below 60% load partializing turbine admission allows efficiency gain of up to 4.7p.p. Abstract: The Allam Cycle is a highly regenerative oxy-combustion cycle with very promising net electrical efficiency, low expected cost and near-zero emissions (being directly suitable for carbon capture and storage). In this cycle, the CO2 produced from the oxy-combustion is recycled as temperature moderator and the excess CO2 produced can be captured and stored. In this work, a detailed part-load model of the Allam Cycle is developed considering the off-design performance maps for the compressors, pumps and the turbine. To adjust the cycle load, different part-load control strategies are devised by combining turbine partial-admission, compressor variable guide vanes (at compressor inlet and diffuser) and minimum cycle pressure variation. These control strategies are compared at various part-load conditions ranging from 90% down to 20%. The study shows that the optimal control strategy varies depending on the cycle load. Furthermore, the increase of part-load cycle efficiency using advanced control strategies can reach up to 4.71 percentage points compared to a conventional strategy employing only variable compressor guide vanes. The research shows that close-to-maximum part-load efficiency can be achieved only with the optimized adjustment of compressors guide vanes and the minimum cycle pressure, while partial admission turbine turns out to be essential at very low loads (15–30% load).